Growth and Neurodevelopmental Outcomes of Extremely Low Birth Weight Infants: A Single Center's Experience - Yung-Chieh Lin; Yuh-Jyh Lin; Chyi-Her Lin (Elsevier, 2011)
The outcome of extremely low birth weight (ELBW, ≤1000 g) infants has recently been improved in Taiwan. However, their postdischarge anthropometry and development have seldom been explored. We report these results for ELBW infants at corrected age of 2 years in a tertiary care center. Methods: This descriptive and retrospective study enrolled ELBW infants discharged alive from a tertiary care center from January 2004 to December 2007. A scheduled follow-up program up to 2-year corrected age was tightly controlled by a case manager. Bayley Scales of Infant Development-Second Edition, representing the mean±1 standard deviation as 100±15 in normal population, was used to assess infants' development. An index less than 70 was regarded as abnormal. Anthropometry, including body weight (BW), body length (BL), and head circumference (HC), against the growth standard from the World Health Organization was assessed. Growth delay was defined as growth parameters below the 10th percentile values. Results: One hundred ELBW infants were enrolled. Eighty of them were discharged alive (80% surviving), and their follow-up rates were 91% at 6 months, 90% at 12 months, and 83% at 24 months corrected ages. The 2-year survival rate was 75%. The percentages of delayed growth in BW/BL/HC, presented as (male vs. female), were (33/41/37 vs. 38/25/45) at 6 months, (31/31/50 vs. 41/22/37) at 12 months, and (39/36/54 vs. 26/29/38) at 24 months. The negative means of the Z score for BW/BL/HC in both genders indicated ELBW infants had significant growth delay compared with those of the normal population. The index of Bayley scales was significantly lower in ELBW infants than that in normal population at each age. Male infants had lower mental development index and psychomotor development index at 2 years than females. About 61% of those with BW less than 750 g died or had neurodevelopmental impairment. Conclusion: ELBW infants have a high incidence of growth and developmental delay at corrected age of 2 years, particularly in male infants or those with BW less than 750 g. This study reveals that ELBW infants require well predischarge planning and postdischarge follow-up.